Towards a Reconstruction of Enlightenment Values in a Changing World (part II) - Abdellatif, Kamal (Münster journal for Islamic and philosophical studies, 2023)
‭ ‬Those who declare the failure of the enlightenment project in Arab societies forget that the efforts of thinkers in the era of‭ ‬the Arab Awakening‭ ‬“Nahda”‭, ‬who worked to instill the values of reason‭, ‬criticism‭, ‬freedom and progress in our culture‭, ‬were not only theoretical but more‭ ‬like a process of confrontation‭, ‬a confrontation within the limits of thinking and language‭, ‬and a confrontation with a history‭ ‬of tyranny A history of fundamentalist thought‭. ‬They may also have forgotten that the new theoretical trends that are linked to‭ ‬what we call self-aware rationality‭, ‬historical rationality and critical rationality are in depth the outcome of the various efforts undertaken by the first and second generation of thinkers during the Arab Awakening in their reading of history and tradition‭, ‬since the middle and end of the nineteenth century when the productive interaction with the spirit of modernity began‭. ‬Arab‭ ‬societies‭, ‬while continuing their aspiration to build a modern society‭, ‬need the principles and premises of contemporary thought‭, ‬and at the heart of these principles are the gains of the Enlightenment philosophy that is capable of rebuilding society‭, ‬thought and history again‭.‬